2020
DOI: 10.1080/15548627.2020.1741318
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin TPR (translocated promoter region, nuclear basket protein) upregulation alters MTOR-HSF1 trails and suppresses autophagy induction in ependymoma

Abstract: Children with ependymoma have high mortality rates because ependymoma is resistant to conventional therapy. Genomic and transcriptomic studies have identified potential targets as significantly altered genes in ependymoma patients. Although several candidate oncogenes in ependymoma were recently reported, the detailed mechanisms for the roles of these candidate oncogenes in ependymoma progression remain unclear. Here, we report an oncogenic role of the nucleoporin TPR (translocated promoter region, nuclear bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Cells were then rinsed and incubated with secondary antibodies in 4% BSA/PBS (1:500 dilution) for 2 h at room temperature. After washing with PBS, coverslips were mounted on slides using ProLong Diamond Antifade reagent with DAPI (Invitrogen, P36966), and observed on a confocal laser-scanning microscope with 60X PlanApo/1.45NA DIC objective (Olympus, FV10i-LIV), as previously described [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were then rinsed and incubated with secondary antibodies in 4% BSA/PBS (1:500 dilution) for 2 h at room temperature. After washing with PBS, coverslips were mounted on slides using ProLong Diamond Antifade reagent with DAPI (Invitrogen, P36966), and observed on a confocal laser-scanning microscope with 60X PlanApo/1.45NA DIC objective (Olympus, FV10i-LIV), as previously described [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear/cytoplasmic fractionation analysis was performed using nuclear and cytoplasmic extraction reagents according to the manufacturer's protocol (Thermo Scientific, 78840), as previously described [ 25 , 27 ]. Cytoplasmic and nuclear extracts were then subjected to immunoblotting analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of autophagy in ependymoma has not been specifically investigated so far. However, a study concerning the role of nucleoporin TPR upregulation within this tumour attracted the interest of researchers in regard to its connection with autophagy, given the existing correlation between TPR depletion and autophagy induction in HeLa cells [ 126 ]. By analysing mRNA expression levels of autophagy-related proteins, Dewi’s research team found that ATG3 , ATG5 , ATG12, and Beclin 1 expression is significantly downregulated in ependymoma patients [ 127 ].…”
Section: Autophagy In Childhood Brain Tumoursmentioning
confidence: 99%
“…TPR has been since implicated in a variety of nuclear functions, including mitosis, regulation of transcription, chromatin organization, and nuclear transport (Snow and Paschal, 2014). A study showed that high expression of TPR is associated with ependymoma and TPR may act as a biomarker for ependymoma (Dewi et al, 2020). TPR is also related to some other cancer progression, including colorectal cancer (Dewi et al, 2018), lung adenocarcinoma (Choi et al, 2014) and so on.…”
Section: Introductionmentioning
confidence: 99%